Predicted distribution of a rare and understudied forest carnivore: Humboldt marten (Martes caurina humboldtensis) - Katie M. Moriarty; Joel Thompson; Matthew Delheimer; Brent R. Barry; Mark Linnell; Taal Levi; Keith Hamm; Desiree Early; Holly Gamblin; Micaela Szykman Gunther; Jordan Ellison; Janet S. Prevéy; et al. (PeerJ, 2021)
Background Many mammalian species have experienced range contractions. Following a reduction in distribution that has resulted in apparently small and disjunct populations, the Humboldt marten (Martes caurina humboldtensis) was recently designated as federally Threatened and state Endangered. This subspecies of Pacific marten occurring in coastal Oregon and northern California, also known as coastal martens, appear unlike martens that occur in snow-associated regions in that vegetation associations appear to differ widely between Humboldt marten populations. We expected current distributions represent realized niches, but estimating factors associated with long-term occurrence was challenging for this rare and little-known species. Here, we assessed the predicted contemporary distribution of Humboldt martens and interpret our findings as hypotheses correlated with the subspecies’ niche to inform strategic conservation actions. Methods We modeled Humboldt marten distribution using a maximum entropy (Maxent) approach. We spatially-thinned 10,229 marten locations collected from 1996–2020 by applying a minimum distance of 500-m between locations, resulting in 384 locations used to assess correlations of marten occurrence with biotic and abiotic variables. We independently optimized the spatial scale of each variable and focused development of model variables on biotic associations (e.g., hypothesized relationships with forest conditions), given that abiotic factors such as precipitation are largely static and not alterable within a management context. Results Humboldt marten locations were positively associated with increased shrub cover (salal (Gautheria shallon)), mast producing trees (e.g., tanoak, Notholithocarpus densiflorus), increased pine (Pinus sp.) proportion of total basal area, annual precipitation at home-range spatial scales, low and high amounts of canopy cover and slope, and cooler August temperatures. Unlike other recent literature, we found little evidence that Humboldt martens were associated with old-growth structural indices. This case study provides an example of how limited information on rare or lesser-known species can lead to differing interpretations, emphasizing the need for study-level replication in ecology. Humboldt marten conservation would benefit from continued survey effort to clarify range extent, population sizes, and fine-scale habitat use.